The properties of “Khurmo” variety of cotton - Zakir Rajabov Pulatovich (Zien Journals, 2023)
Relevance and necessity of the research topic. Among technical crops, the most valuable crop is cotton. It is grown mainly for its fiber. Cotton fiber is the most widely used product in the textile industry, accounting for about half of the fibers produced worldwide. "Cotton is a source of income for approximately 1 billion people".
Keywords: Cotton; Khurmo; fiber